From Paper, to Microform, to Digital? Serials at The ArQuives: Canada’s LGBTQ2+ Archives - McLeod, Donald W. (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2019)
The ArQuives: Canada’s LGBTQ2+ Library and Archives, founded in 1973, holds one of the largest collections of queer serials in the world. The more than 10,000 titles are mostly in paper, but formats have been evolving. Beginning in the 1980s, the ArQuives participated in small microfilming projects. Microfilming of the collection greatly increased in 2005, when Primary Source Microfilm (PSM) undertook a large project to film a portion of the collection, resulting in 211 reels devoted to international gay and lesbian periodicals and newsletters. The PSM project was later repurposed and expanded by Gale Cengage, beginning in 2015, and forms part of its Archives of Sexuality and Gender online product. This paper examines the evolution of the ArQuives’ serials holdings from paper to microform to digital formats and explores recent in-house digitization efforts and future prospects for expanding access to these materials.